The Editorial Work of Gianni Toti and Latin American Literature (Anclajes, 2021)
The essay presents the editorial activity of Gianni Toti, a versatile Italian intellectual who has worked as a cultural mediator between Italy and Latin America since the 1960s. Specifically, it examines work carried out in the 1990s with the Fahrenheit 451 publishing house where Toti founded and directed two collections in which highlighted Latin American authors.
Keywords: Intercultural mediation; Hispanic American literature reception; Hispanic American literature; editorial policy; Italian culture